Inside the whirlwind the book of Job through African eyes - Carter Jason A.; Walls, Andrew F. (Andrew Finlay) (Eugene, Oregon : Pickwick Publications, 2017)
How would ordinary African Christians interpret the figure and book of Job--the quintessential biblical book on suffering--from contexts of extreme poverty, tropical disease, and rampant suffering? How do African Christians culturally understand issues of theodicy and the nature of evil? What role does the devil play in African Pentecostalism? How does the biblical lament empower faith and foster hope for people living with HIV/AIDS? In what way does a theology of (eschatological) hope inform the spirituality and prayers of ordinary African believers in the midst of suffering? Inside the Whirlwind offers insight on these fascinating questions. Based upon the perspectives of Fang Christians in Spanish-speaking Equatorial Guinea (Central Africa), the thematic and theological reflections on evil, suffering, and hope emerging from sermons and Bible studies on the book of Job offer a remarkable window to view the main theological issues shaping grassroots African Christianity in the twenty-first century.
Includes bibliographical references and indexes.
Description based on print version record.
Master record variable field(s) change: 072, 082 - OCLC control number change
Keywords: Bible. -- Criticism, interpretation, etc; Bible; Christianity -- Africa; Christianity -- Equatorial Guinea; Christianity; Africa; Equatorial Guinea; RELIGION / Christianity / History; Criticism, interpretation, etc; Electronic books